HUBUNGAN PENATALAKSANAAN TUGAS KESEHATAN KELUARGA DENGAN KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS MARTAPURA - Yohana A. Sitanggang; Nuzul Qur'aniati; Ilya Krisnana (Universitas Airlangga, 2014)
Introduction: Upper respiratory tract infection ( URTI ) is an acute respiratory infection that attacks human with the most number of infection are infants. Family has a function as a family health care that can be seen by five tasks of family health, the role of family is very needed for the prevention to reduce morbidity and mortality rates in toddlers, especially in cases of URTI. This study were aimed to analyze the relationship between implementation of family health tasks with URTI incidence in toddlers patients.Method: This study used correlation descriptive design. The samples were 147 families who have toddlers had experienced URTI and have been visit Puskesmas Martapura during November 2013. The variables are family health tasks and incindents of URTI in toddlers.Samples were taken by consecutive sampling that appropiate with inclusion and exclusion criterias. The data were analyzed by Spearman's rho with significance level (p) ≤ 0.05.Result: The result showed that family health task and incindents of URTI in toddlers did have negative significance correlation (r) = -0,387 and (p) = 0,01.Discussion: Implementation of family health tasks had a weak correlation with URTI incidence in toddlers patients. It is recommended to the stake holder of URTI disease in Puskesmas Martapura to continue give a socialization about URTI definition, sign and symptom, and right treatment especially for toddler with URTI disease. It is necessary futher research to analyze the correlation between toddler characteristics with insindece of URTI.